Importance Counseling Danger Smoking in Maintaining Public Health in the Region Work Health Center of Sawah Lebar, Bengkulu City - Denni Rahmiati; Zuriana, Qonitha; Pebrianti, Nursyah; Handayani, Tita Septi (Universitas Dehasen Bengkulu, 2025)
Smoking behavior is one of the public health problems that have serious impact on individuals and society as a whole. In the context of public health, a deep understanding of smoking behavior is very important, especially in the work area of the Health Center where public health services are faced with complex challenges. This activity aims to provide motivation and understanding of the importance of education. By using qualitative descriptive methods/data collection by means of interviews, documentation and direct observation. The results of real work lectures to the community increase motivation and awareness in the community to no longer smoke through counseling or health education to wards change in public knowledge about the dangers of smoking through a health education approach.